2008
DOI: 10.1620/tjem.215.313
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin 4 mRNA Levels in Neuromuscular Tissues of Wild-type and Dystrophin-deficient Mice

Abstract: Aquaporin (AQP) 4 is a water-specific channel protein and is abundant in central nervous tissues and skeletal muscles. Recently, the AQP4 molecule has been increasingly highlighted in its pathophysiological role of several neurological diseases, such as stroke, muscular dystrophy and neuromyelitis optica. We therefore measured the levels of AQP4 mRNA and glyceraldehyde-3 phosphate dehydrogenase mRNA (an internal control) in muscle and brain tissues of wild-type mice (C57BL10/ScSn) and age-matched dystrophindef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…With AQP4 being the most abundant aquaporin in the brain, the number of mRNA copies in murine cardiomyocytes has been estimated at around 11 % of that in the fast-twitch skeletal muscle and only 2.5 % of that in the cerebellum [38]. However, to evaluate the importance of function, cellular localization may be as significant as quantity.…”
Section: Aqp4 Localization In the Mouse Heartmentioning
confidence: 99%
See 1 more Smart Citation
“…With AQP4 being the most abundant aquaporin in the brain, the number of mRNA copies in murine cardiomyocytes has been estimated at around 11 % of that in the fast-twitch skeletal muscle and only 2.5 % of that in the cerebellum [38]. However, to evaluate the importance of function, cellular localization may be as significant as quantity.…”
Section: Aqp4 Localization In the Mouse Heartmentioning
confidence: 99%
“…AQP4 expression in the human heart was reported to be very low [7]. Only a few studies have addressed the expression and subcellular localization of AQP4 in the heart, with inconsistent results [7,38,44]. Thus, it is currently unclear in which cardiac cells AQP4 is located, where in the cell it is expressed, and how its expression is regulated.…”
Section: Introductionmentioning
confidence: 99%
“…There is little doubt that AQP4's normal function in astrocytes is to enable fast water influx or efflux, driven by osmotic or hydrostatic pressures (Solenov et al, 1997; Yang et al, 2008). It has been reported that rat spinal cord tissue has the highest expression levels of AQP4 among all AQP4-expressing organs, including several different brain regions as well as various muscles including heart tissue (Shibuya et al, 2008). Widespread and high expression levels of AQP4 in mammalian spinal cords suggest the importance of potentially altered AQP4 functions in different pathological spinal conditions.…”
Section: Aqp4mentioning
confidence: 99%
“…The concentration of AQP4 mRNA content was estimated by real-time quantitative RT-PCR as described previously [20]. The oligonucleotide primers were designed from the mouse AQP4 sequence (Entrez U88623): sense strand, 5'-GAAAACCCCTTACCTGTGG-3'; antisense strand, 5'-AGCTGGCAAAAATAGTGA-3'.…”
Section: Methodsmentioning
confidence: 99%